Performance analysis of weighted non-coherent receiver for UWB-PPM signal in multipath channels - WU Jian-jun; LIANG Qing-lin; XIANG Hai-ge (Tongxin xuebao)
The BER performance expressions and weighting coefficients of the weighted non-coherent receiver for the UWB-PPM signal were analytically derived.Subsequently,the analytical results were validated via Monte-Carlo simula-tion,and the impacts of the sub-interval width and the timing error were also numerical analyzed.It is illustrated that the weighted receiver is at least 3dB superior to the conventional non-coherent receiver,and is robust to the variations of sub-integration width and the timing error.